Implementation of Law Number 16 of 2019 on Marriage Concerning the Minimum Age of Marriage at the Office of Religious Affairs (KUA) in Barru District, Barru Regency - Wahyu Az; Usamah Mahmud (Meraja journal, 2025)
[Full Paper] to pdf Copyright (c) 2025 Meraja journal